Value of Systemic Staging in Asymptomatic Early Breast Cancer - Gregório Pinheiro Soares; Allan Andresson Lima Pereira; Mariana Silva Vilas Boas; Victor Van Vaisberg; Maria Cristina Figueroa Magalhães; Rudinei Diogo Marques Linck; Max Senna Mano (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective Metastases are rare in early breast cancer (EBC), and international guidelines recommend against routine systemic staging for asymptomatic patients. However, imaging exams remain widely employed in the clinical practice. The aim of the present study is to evaluate the value of imaging for systemic staging in EBC. Methods A retrospective analysis of newly-diagnosed breast cancer (BC) patients was performed. Clinical data including BC subtype, stage, presence of symptoms at diagnosis and instrumental procedures performed for staging were recorded. Results A total of 753 patients were included, with a median age of 57 years. The majority of the patients underwent at least 1 imaging procedure (91%); had invasive ductal carcinoma (83.5%); histological grade 2 (51.4%); stage II (61.8%); and luminal subtype (67.9%). Among the 685 (91%) patients who underwent any radiologic staging, distant metastases (DMs) were detected in 32 (4.7%). In the univariate analyses, stage IIb and pathological lymph node involvement (pN1) showed a statistically significant association with the presence of DMs, versus only a trend for triple negative and human epidermal growth factor receptor 2 (Her2) positive subtype. In an exploratory analysis performed in this same subgroup, when unfavorable biology (triple negative or Her2 positive) was present, patients had a DM rate of 14.4%, one of the highest reported at this stage of the disease. Conclusion Early breast cancer has a low prevalence of DM at the initial evaluation, and systemic staging of asymptomatic, unselected patients is not warranted as a routine practice. However, we have identified subgroups of patients to whom a full staging could be indicated.